Intensity Analysis to Study the Dynamics of Reforestation in the Rio Doce Water Basin, Brazil - Bilintoh, Thomas Mumuni (Frontiers in Remote Sensing, 2022)
Conservationists routinely require methods to analyze the effects of conservation interventions such as reforestation. Although methods to measure the effects of reforestation abound, these methods often fail to track and communicate the complexities of reforestation interventions. This paper uses intensity analysis to analyze the effects of reforestation intervention in Brazil’s Rio Doce water basin. In particular, this paper uses intensity analysis to study the effects of reforestation on three land cover categories in Brazil’s Rio Doce water basin. The illustrative approach analyzes the temporal difference of forest in three land cover maps at time points 1998, 2008, and 2015 from the Rio Doce water basin, Brazil, where each map has four land cover categories: forest formation, pasture, mosaic of agriculture and pasture, and urban infrastructure. Interval level intensity indicates that change is faster during the second time interval (1998–2008). The results from the categorical level intensity show that the forest formation and the mosaic of agriculture and pasture are active gainers during both time intervals, while pasture is an active loser. Forest formation targets the mosaic of agriculture and pasture more intensively at the interval level during the first time interval. Forest formation gains the most from a mosaic of agriculture and pasture while at the same time targeting the mosaic of agriculture and pasture during the second time interval. The mosaic of agriculture and pasture gains the most from both forest formation and pasture during both time intervals but targets pasture. The results for the second time interval show that the reforestation process in the Rio Doce water basin, Brazil, only forced the farmers to move to other forest covers in the vicinity. This process constitutes exchange, which accounts for more than half of the change during the second time interval, and thus contributes 0 to the net change of forest.